The Correlation between Self-Care and Quality of Life in Type 2 Diabetes Mellitus Patients at the Sei Rampa Health Center - Sri Lestari Ramadhani Nasution; Winda Adelia Lubis; Ermi Girsang; Abednego Karo Sekali (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Type 2 diabetes mellitus (T2DM) can substantially reduce patients’ quality of life (QoL). Self-care is expected to lessen this burden, but evidence across key self-care domains in primary care is still limited. This study aims to identify how strong and significant the relationship between these two variables is: self-care and quality of life. A sequential explanatory mixed-methods study was conducted at the Sei Rampah Community Health Center. Quantitatively, 136 T2DM patients completed a survey; Pearson’s correlation tested associations between five self-care domains (diet, physical activity, medication therapy, availability of blood-glucose monitoring equipment, and diabetes knowledge) and QoL. Qualitatively, in-depth interviews with eight patients explored daily self-care experiences; transcripts were coded and thematically analyzed using CAQDAS/NVivo following the Miles and Huberman framework. Ethical approval was granted by Universitas Prima Indonesia. All self-care domains were significantly associated with better QoL (p < 0.001). Interview data explained the quantitative patterns: diet adherence was constrained by financial limitations, eating habits, and limited healthy menu variety; physical activity was generally light and inconsistent due to fatigue, age, motivation, and family support; medication adherence was relatively high but lapses occurred without reminders; routine glucose monitoring was uncommon because glucometers and strips were costly and health literacy was limited; and stronger diabetes knowledge, often reinforced by family, supported more consistent self-care behaviors. Programs should strengthen feasible diet and activity routines, support adherence with reminders, expand affordable access to glucometers/strips, and intensify education by engaging family support to improve QoL. Keywords: T2DM, Self-Care, Quality of Life, Medication Adherence, Glucose Monitoring, Primary Care.